A kinematic comparison between long-line and cross-court top spin forehand in competitive table tennis players - Malagoli Lanzoni, I.; Bartolomei, S.; Di Michele, R.; Fantozzi, S. (Journal of Sports Sciences, 2018)
The aim of the present study was to compare the biomechanical characteristics of the table tennis top spin shot when played cross-court (CC) or long-line (LL) in competitive table tennis players. Seven national level players respectively completed 10 long-line and 10 cross-court top spin shots responding to a standard ball machine. A stereophotogrammetric system was used to track body segments while executing the motion. Significantly more flexed right knee and elbow angles were measured at the moment of maximum velocity of the racket (MMV) in LL. In addition, significantly greater angles between the feet and the table and between the shoulders and the table at the MMV, indicated more pronounced rotation angles of the lower upper and upper-body in LL compared to CC with respect to the table. A higher inclination of the racket at the MMV was found in LL. The elbow flexion and the racket inclination may be associated to the direction of the shot. The present findings show that kinematic differences exist between the LL and the CC topspin forehand in competitive table tennis players. Coaches should be aware of these differences to adopt the optimal teaching strategies and to reproduce proper joint angles during training.